An in situ prepared photo-luminescent transparent biocompatible hyperbranched epoxy/carbon dot nanocomposite. Issue 91 (9th October 2015) - De, Bibekananda; Kumar, Manishekhar; Mandal, Biman B.; Karak, Niranjan
<x xml:space="preserve">Abstract</x> An excitation wavelength dependent photo-luminescent, high performance, transparent and biocompatible hyperbranched epoxy/carbon dot nanocomposite was obtained through in situ technique.